Evolution and changes of tourism in Macedonia in the post-socialist period (1991–2018) - Iliev, Dejan (Uniwersytet Gdanski, 2019)
The study provides a historical and contextual analysis of the evolution of tourism in Macedonia. The time scope is defined as the period between 1991 and in 2018. The study investigates the tourism development in Macedonia in the post-socialist period of the country, using the Butler (1980) Tourist Area Life Cycle (TALC) model as an analytical tool. The model provides a framework to explain the complex processes of the development and changes in tourism in the country over the years. For this purpose, an analysis of secondary data sources is implemented to find the changes in the evolutionary stages of tourism development. The findings show that tourism in Macedonia is in a stage of development, and that it has not yet reached the consolidation stage. Lastly, the study offers a better understanding of how tourism in Macedonia is changing in the complex post-socialist period.
Keywords: tourism development, evolution, TALC model, post-socialist period, Macedonia